GH overexpression causes muscle hypertrophy independent from local IGF-I in a zebrafish transgenic model - Kuradomi, Rafael Yutaka (2011)
The aim of the present study was to analyse the morphology of white skeletal muscle in males and females from the GH-transgenic zebrafish(Danio rerio) lineage F0104, comparing the expression of genes related to the somatotrophic axis and myogenesis. Histological analysis demonstrated that transgenic fish presented enhanced muscle hypertrophy when compared to non-transgenic fish, with transgenic females being more hypertrophic than transgenic males. The expression of genes related to muscle growth revealed that transgenic hypertrophy is independent from local induction of insulin-like growth factor 1 gene (igf1). In addition, transgenic males exhibited significant induction of myogenin gene (myog) expression, indicating that myog may mediate hypertrophic growth in zebrafish males overexpressing GH. Induction of the a-actin gene (acta1) in males, independently from transgenesis, also was observed. There were no significant differences in total protein content from the muscle. Our results show that muscle hypertrophy is independent from muscle igf1, and is likely to be a direct effect of excess circulating GH and/or IGF1 in this transgenic zebrafish lineage.